From Coastal Resource Potential to Community Welfare: The Mediating Role of Marine Agro-Ecotourism Performance in Northern Coastal East Java, Indonesia - Mukti Ali; Akhmad Fauzi; Nuriyah Yuliati; Mubarokah (Postgraduate, University of Mataram, 2026)
This study theoretically examines the determinants of Marine Agroecotourism Performance and its implications for the welfare of coastal communities using a Partial Least Squares-based Structural Equation Modelling (PLS-SEM) approach. The research model integrates Coastal Resource Potential, Socio-Cultural Aspects, and Community Empowerment as the main determinants of marine agroecotourism performance with data from 385 respondents. The results of the analysis show that these three constructs have a positive and significant effect on marine agroecotourism performance, with coastal resource potential as the most dominant factor. Furthermore, marine agroecotourism performance was found to have a significant effect on community welfare, reflecting improvements in the economic, social, and quality of life aspects of local communities. The novelty of this study lies in the development of an integrative model that links ecological, socio-cultural, and community empowerment dimensions in the context of marine agroecotourism, as well as in testing the role of tourism performance as a mediating mechanism for coastal community welfare. These findings enrich the literature on sustainable tourism and coastal area development, and provide policy implications that emphasise the importance of community-based approaches and resource sustainability in regional tourism development.